Attenuation of immune‐mediated bone marrow damage in conventionally housed mice. Issue 2 (2nd January 2020) - Li, Jun; Dubois, Wendy; Thovarai, Vishal; Wu, Zhijie; Feng, Xingmin; Peat, Tyler; Zhang, Shuling; Sen, Shurjo K.; Trinchieri, Giorgio; Chen, Jichun; Mock, Beverly A.; Young, Neal S.
Abstract: In humans, bone marrow (BM) failure syndromes, both constitutional and acquired, predispose to myeloid malignancies. We have modeled acquired immune aplastic anemia, the paradigmatic disease of these syndromes, in the mouse by infusing lymph node cells from specific pathogen‐free (SPF) CD45.1 congenic C57BL/6 (B6) donors into hybrid CByB6F1 recipients housed either in conventional (CVB) or SPF facilities. The severity of BM damage was reduced in CVB recipients; they also had reduced levels of CD44 + CD62L − effector memory T cells, reduced numbers of donor‐type CD44 + T cells, and reduced expansion of donor‐type CD8 T cells carrying T‐cell receptor β‐variable regions 07, 11, and 17. Analyses of fecal samples through 16S ribosomal RNA amplicon sequencing revealed greater gut microbial alpha diversity in CVB mice relative to that of SPF mice. Thus, the presence of a broader spectrum of gut microorganisms in CVB‐housed CByB6F1 could have primed recipient animal's immune system leading to suppression of allogeneic donor T‐cell activation and expansion and attenuation of host BM destruction. These results suggest the potential benefit of diverse gut microbiota in patients receiving BM transplants.